The effect of the health belief model-based educational program on physical activity beliefs and behaviors of university students - KADIOĞLU, HASİBE (My University, 2022)
Aim This study was conducted to determine the effect of the education program based on the Health Belief Model (HBM) on the physical activity beliefs and behaviors of university students. Subject and methods This quasi-experimental study was carried out with one experiment and one control group where a pre-test and post-test were applied to the participant. The study included 129 participants (experimental group = 61, control group = 68) studying at two universities between March-September 2019. A 4-week HBM-based training program was applied to the students in the experimental group. Data were collected with the \"Personal Information Form,\" \"International Physical Activity Questionnaire (IPAQ)\" and \"Exercise Health Belief Model Scale (EHBMS).\" Chi-square test, T-test for dependent and independent groups, Wilcoxon sign test, and Mann-Whitney U tests were used in the evaluation of the data. Result The EHBMS (p = 0.009) and MET (p=0.000) total score averages of the experimental group were found to be statistically significantly higher than the control group in the post-test. Conclusion We determined that the HBM-based education program implemented within the scope of this study positively affects the physical activity beliefs and behaviors of the students. Nurses studying with students can use this program as a guide.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); İş Sağlığı ve Terapisi; Güvenlik Araştırması; Sağlık (sosyal bilimler); Genel Sosyal Bilimler; Halk, Çevre ve İş Sağlığı; Epidemiyoloji; Sağlık Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Occupational Therapy; Safety Research; Health (social science); General Social Sciences; Public Health, Environmental and Occupational Health; Epidemiology; Health Sciences; Social Sciences & Humanities; Exercise Health Belief Model Scale; Physical activity; Nursing; Health Belief Model; INTERVENTION; EXERCISE; RELIABILITY; PREVALENCE; EFFICACY; FITNESS